Two Improved Acquisition Systems for Deep Subsurface Exploration - Liu, Nengchao; Yao, Gang; Zou, Zhihui; Wang, Shangxu; Wu, Di; Li, Xiang; Zhou, Jianye (Frontiers in Earth Science, 2022)
Present land seismic surveys mainly focus on acquiring reflection data. The maximum offset is usually 1 to 1.5 times the depth of targets. Limited offset results in that the acquired diving waves only penetrate the shallow parts of the Earth model, far from the targets. Thus, the reflection data are used to build the deep part of the velocity model with migration velocity analysis. However, two issues challenge the success of velocity model building. Firstly, incomplete information. Limited offsets lead to a narrow aperture of observation, which results in an under-determined inversion system. One manifestation is the trade-off between the depth of interfaces/reflectors and the average velocity above them. Secondly, low signal-to-noise (S/N) ratios. Complex near-surface conditions and geologic structures lead to low S/N ratios for reflection data, which fails to build velocity with reflection data. The fundamental solution to these two issues is to acquire better data with an improved acquisition system. In this work, we propose two types of modified geometries to enhance the penetration depth of the diving waves, especially the first arrivals, which can be used to build a deeper velocity model effectively. The Type-I geometry adds extra sparse sources on the extension line of the normal acquisition geometry, whereas the Type-II geometry deploys extra sparse receivers on the extension line. Consequently, the new acquisition system includes ultra-large offsets, which acquire diving waves from the deep subsurface. These diving waves, including waveform and first-break time, are particularly useful for recovering deeper velocity, which has paramount significance for the exploration of deep and ultra-deep hydrocarbon reservoirs. Synthetical and field data examples preliminarily demonstrated the feasibility of this improved acquisition system.